Sowing the seeds of tomorrow, one school garden at a time - Borelli, Teresa; Tognoli, Flora (2024)
Learn how the Alliance is delivering an integrated module on neglected and underutilized species (NUS) targeting primary school children aged 7 to 11 in Burkina Faso. The module fosters intergenerational knowledge exchange, whereby children are encouraged to interview grandparents and elders within their communities to learn the lore and traditions associated with these NUS. Quizzes and competitions make learning fun and lessons are complemented with practical, hands-on training in which children are involved in establishing a school garden and learn to grow and care for NUS.